Male wing dimorphism in Australian Amphientomidae (Psocodea) - Taylor, Christopher (n/a, 2012)
Polymorphism in wing development is found in many families of Psocodea, both within and between sexes. However,records of polymorphism in Amphientomidae are not common, with dimorphism between sexes known for some species,but no records to date of within-sex dimorphism. A new species of Amphientomidae from Barrow Island in northernWestern Australia, as well as being the first Australian species described from multiple specimens, represents the first known case of within-sex dimorphism for Amphientomidae, with both macropterous and brachypterous males collected.